CARL DIEM – A SIGNIFICANT SPORTS PERSONALITY FOR GERMANY, EUROPE, AND BULGARIA ATTEMPT AT ANALYSIS AND ASSESSMENT - Jörg Schenk (Journal of Applied Sports Sciences)
The German Carl Diem is considered one of the most outstanding sports personalities and Olympic promoters of modern times and was not only relevant to sports development in and for Germany but also abroad. His work unfolded especially in the first half of the 20th century but led to highly contradictory assessments of his person and his work due to the circumstances of the time and political developments in Germany and Europe. It becomes apparent that in contrast to Germany, where Diem is now almost forgotten despite an almost incalculable oeuvre and is only known to sports historians, in Bulgaria, where he created the essential basis for the establishment and structure of the “State Higher School for Physical Education”, later “National Sports Academy ‘Vasil Levski’”, and thus the academic training of sports teachers with his “Organizational Plan for Physical Education in Bulgaria”, there was initially no mention of him after 1944 and only from the 1990s of the last century at least some few mentions. This article uses an overview of the academic literature to shed light on Diem’s changed reception in Germany as well as the deficient research situation on him in Bulgaria.